Gaya Penyampaian Presenter Program Acara “Tonight Show” Dalam Menarik Minat Penonton - Mochammad Sinung Restendy; Mishbahu Rahmah; Reza Muh Edy Putra Perdana; Ziadatul Fauziah Aryati (Journal of Communication Studies, 2021)
Each television station presents various programs to attract public interest. No exception with Net TV. This television station presents a Talk show program entitled "Tonight Show". The Tonight Show program was hosted by famous presenters Vincent and Desta. The Tonight Show was packed with talks between presenters and guest stars, to make the event more attractive, there were various games that were no less fun to entertain the audience. The Tonight Show hosts have their own delivery styles. With different colors Vincent and Desta can combine their communication styles into one interesting mix. Many people have their interest in the Tonight Show because the presenter's style is not boring. The theoretical runway used is the theory of uses and grastification belonging to Blumer and Kaltz.